ANALISIS FOTO MAKRO TERHADAP KEKASARAN BAJA ST 60 HASIL PEMBUBUTAN FACING DI MESIN CNC HARDINGE - Syaiful, Syaiful; Panggabean, Hasbullah (Jurnal Rekayasa Mesin, 2025)
Technological advances have made the manufacturing sector an industry that needs to develop and compete globally, one of which is CNC machines which produce quality products for industrial needs. In producing a material at CNC machine, the latest design software is needed, namely Autodesk Fusion 360. Apart from lest, on then machine processing, it is desired to produce a material surface with a good roughness value. The desired result of this research is to analyze roughness value towards facing turning results on CNC machines for variations in spindle speed, namely 410 rpm, 450 rpm, 660 rpm, 900 rpm, 1100 rpm and 1200 rpm using carbide chisels and dromus coolant. The roughness of the facing surface can be assessed using a Surface Roughness Tester and analyzing the material structure using macro photos. The results of specimen testing showed that the smallest roughness value occurred of a spindle speed of 1200 rpm with a value of Ra = 0.810 µm and the output of observations make use macro photos represent that the roughness structure of the material was very smooth compared to the production process on CNC machines using other spindle speeds.